The Pancreatic changes affecting glucose homeostasis in transfusion dependent β- thalassemia (TDT): a short review: Pancreatic changes and glucose homeostasis in β-thalassemia - De Sanctis, Vincenzo; Soliman, Ashraf; Tzoulis, Ploutarchos; Daar, Shahina; Fiscina, Bernadette; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2021)
Background : The natural history of the glycometabolic state in transfusion-dependent β-thalassemia (TDT) patients is characterized by a deterioration of glucose tolerance over time. Aims: This review depicts our current knowledges on the complex and multifacet pathophysiologic mechanisms implicated in the development of alteration of glucose homeostasis in patients with TDT. Search strategy: A systematic search was done on December 2020 including Web of Science (ISI), Scopus, PubMed, Embase, and Scholar for papers published in the last 20 years. Moreover, we checked the reference lists of the relevant articles and previously performed reviews for additional pertinent studies. The personal experience on the care of patients with thalassemias is also reported. Conclusion: A regular packed red blood cells (PRBCs) transfusion program, optimization of chelation therapy, and prevention and treatment of liver infections are critical to achieve adequate glucometabolic control in TDT patients. Many exciting opportunities remain for further research and therapeutic development.